(untitled) (Research, Society and Development, 2022)
This article deals with the abuse of forms of marketing communication that associate characters with food products aimed at children. Its purpose is to analyze the circumstances in which such advertising strategy may be considered abusive according to legal rules. Based on the instrumental legal-dogmatic aspect, it is a theoretical study based on Brazilian legislation, jurisprudence and doctrine, as well as, subsidiarily, on foreign and international standards. It uses the deductive approach method; comparative, interpretive and analytical procedures; and bibliographic and documentary research techniques. It addresses the protection – constitutional and infraconstitutional – of the child-consumer, verifying that the legal system recognized its hypervulnerability condition in the consumer market. It presents the specific situation of the child-consumer in the face of advertising, narrowing the issue to food advertising, considering the influence of advertising in the formation of eating habits. Finally, it comes to the conclusion that a persuasive food advertising aimed at children and which uses the strategy of linking characters to food products aimed at children fits the concept of abusiveness inferred from the Consumer Defense Code and the Resolution n. 163 of the National Council for the Rights of Children and Adolescents. However, in the case of the promotion of healthy foods, because the exceptional permissive command of article 2º, § 3, of the aforementioned Resolution n. 163, abusiveness is ruled out due to the exclusion of social harm from the advertising conduct, in other words, due to the non-violation of basic rights of the child-consumer.